1998
DOI: 10.1080/080352598750031392
|View full text |Cite
|
Sign up to set email alerts
|

Septicaemia in an Austrian neonatal intensive care unit: a 7-year analysis

Abstract: The results of blood cultures and clinical data of 101 neonates with 110 episodes of septicaemia during a 7-y study period were reviewed. The overall incidence of culture-proven sepsis within the study period was 6.0 per 100 neonatal intensive care unit admissions and the mortality rate was 14%. Three groups of pathogens accounted for 70% of all isolates: coagulase-negative staphylococci (27%), aerobic Gram-negative rods (24%) and Enterococcus faecalis (19%). Group B streptococcus was the major pathogen of ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…These data show that the aetiology of neonatal bacteraemia is diverse and varies by age, but the reported causative organisms are consistent with previous studies on pathogens causing bacteraemia in neonates 1518. Gram-positive organisms caused the majority of neonatal bacteraemias.…”
Section: Discussionsupporting
confidence: 91%
“…These data show that the aetiology of neonatal bacteraemia is diverse and varies by age, but the reported causative organisms are consistent with previous studies on pathogens causing bacteraemia in neonates 1518. Gram-positive organisms caused the majority of neonatal bacteraemias.…”
Section: Discussionsupporting
confidence: 91%
“…[3] Late onset septicemia (LOS) usually presents after 72 h of age. [5678910] Any newborn with bacterial sepsis is also at risk of meningitis. As such the incidence of meningitis in neonatal sepsis has varied from 0.3% to 3% in various studies, but LOS has been reported to be fairly associated with meningitis; with percentage ranging from 3% to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…72 hours) onset systemic bacterial infection, however, remains a devastating complication and an important cause of morbidity and mortality in these infants. [4][5][6][7] Recent surveys suggest that very low birthweight infants who develop neonatal infection have a significantly increased risk of prolonged oxygen supplementation, 8 a longer hospital stay, 4 5 and higher mortality 5 than patients who are not infected. In both term and preterm infants, early warning signs and symptoms are often minimal, subtle, non-specific, and can easily be misinterpreted as being due to noninfective causes such as transient tachypnoea of the newborn, environmentally induced fluctuation of body temperature, apnoea of prematurity, and acute exacerbations of bronchopulmonary dysplasia.…”
mentioning
confidence: 99%